2013
DOI: 10.15283/ijsc.2013.6.1.1
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of In Vivo Mobilization of Bone Marrow Stem Cells on the Pancreas of Diabetic Albino Rats (A Histological & Immunohistochemical Study)

Abstract: Background and Objectives: The rapidly increasing number of diabetic patients across the world drew the attention to develop more effective therapeutic approaches. Recent investigations on newly differentiated insulin producing cells (IPCs) revealed that they could be derived from embryonic, adult mesenchymal and hematopoietic stem cells. This work was planned to evaluate the role of StemEnhance (Aphanizomenon flos-aquae [AFA] plant extract) in mobilizing naturally occurring bone marrow stem cells as well as i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 37 publications
3
3
0
2
Order By: Relevance
“…Some cells showed features of apoptosis; cells with small darkly stained condensed nuclei (pyknotic nuclei). These findings coincide with a recent research that reported the degeneration of β -cells of islets of Langerhans following STZ injection [29] . These observations could explain the persistent elevation of the random blood sugar level and the significant decrease in the mean area percent of insulin positive reaction in the diabetic group versus the control group detected in the current study.…”
Section: Discussionsupporting
confidence: 93%
“…Some cells showed features of apoptosis; cells with small darkly stained condensed nuclei (pyknotic nuclei). These findings coincide with a recent research that reported the degeneration of β -cells of islets of Langerhans following STZ injection [29] . These observations could explain the persistent elevation of the random blood sugar level and the significant decrease in the mean area percent of insulin positive reaction in the diabetic group versus the control group detected in the current study.…”
Section: Discussionsupporting
confidence: 93%
“…(61) Furthermore, SCE-mobilized BM-HSCs increased the number of insulin-producing cells in islets of Langerhans and reduced blood glucose levels in diabetic rats. (62) Combination of Cyanophyta Aphanizomenon flos-aqua (AFA), Undaria pinnatifida, Polygonum multiflorum, and Cordyceps sinensis may have individual physiological effects, additive effects, and/or synergistic effects with one another, such as serving as both a releasing agent and migration agent. (15) Stem cells circulating in the peripheral blood stream are recruited to sites of tissue in need of repair and regeneration through homing and extravasation.…”
Section: Discussionmentioning
confidence: 99%
“…(66) Bone marrow stem cell mobilization may enhance the intrinsic capability of hepatocytes to proliferate by releasing proliferative cytokines and/or reducing fibrosis, thereby removing the block in the way to hepatocyte proliferation. (67) BMSCs and HSCs were shown to have the ability to become muscle cells, (68) heart cells, (62) endothelium capillary cells, (69) liver cells, (70) lung cells, gut cells, (71) skin cells, (72) and brain cells. (73) As a further illustration, a previous study performed an experiment which not only demonstrated the ability of HSCs to become liver cells upon contact with specific liver derived molecules, but also shows that this process took place within hours in injured liver cells, but the conversion was minimal and delayed when HSCs were exposed to undamaged liver.…”
Section: Discussionmentioning
confidence: 99%
“…Un extrait d'AFA( Aphanizomenon flos aquae-Algue Klamath) nommé StemEnhance ® contient un inhibiteur de la L-sélectine, protéine d'adhésion maintenant les cellules souches dans la moelle osseuse. Il possède des données toxicologiques, précliniques et cliniques connues depuis 10 ans [116,[120][121][122][123]. La L-sélectine est une protéine d'adhésion maintenant les cellules souches dans la moelle osseuse.…”
Section: Nouveau Mobilisateur Naturel De Cellules Souches Cliniquementt Estés Temenhance ® Un Extraitd 'Algue Bleue-verteunclassified